Eastern Efficacy: Political Participation of Post-Communist Women - (:unkn) unknown (My University, 2011)
My dissertation tackles an important question of democratic transition by addressing the apparent lack of political participation, specifically low intensity participation (LIP), of women across much of post-communist Europe. Based on available statistics, it is only in what once was East Germany, and to a lesser extent the Czech Republic, that a low LIP trend is not starkly visible. The regional pattern is contrary to past experiences of women in transition, particularly in Latin America, where women in authoritarian systems pushed for inclusion when democratic space opened. While some research has addressed the issue of high intensity participation (women in elected positions), many of the variables thought to be important (e.g. removal of quotas, electoral structure and party ideology), do not adequately address low LIP among the region's women. Based on 13 months of fieldwork in Poland, eastern Germany, the Czech Republic and Romania I propose that the communist legacy, the lack of an institutionalized women's movement prior to 1989 and gendered job displacement after are related explanations for low female LIP in Eastern and Central Europe during the initial transition period. The absence or limited intensity of one of these variables effects and mediates rates of female LIP, as is the case in eastern Germany (existence of a women's movement) and the Czech Republic (less dramatic gendered job displacement). Additionally, I argue that despite the many changes in women's lives since 1989, particularly related to the eastward expansion of the European Union and the growth of the NGO sector, these three factors remain important for explaining the persistence of low female LIP in much of the region today.
Keywords: Women--Political activity--Europe, Eastern; Women--Political activity--Former communist countries; Post-communism